Composite insulator and preparation method thereof

By using insulator adhesives prepared by materials such as modified alumina microspheres and vinyl trimethoxysilane, the aging problem of composite insulators in high temperature and harsh environments is solved, and its high temperature resistance and water-resistance sealing performance is significantly improved. It extends service life and improves the stability of transmission lines.

CN119207915AActive Publication Date: 2024-12-27SHENZHEN YINXING INSULATOR ELECTRIFIED RAILWAY EQUIP CO LTD

Patent Information

Application Number
CN202411707563.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2024-12-27
Estimated Expiration
2044-11-27

AI Technical Summary

Technical Problem

The epoxy resin glue of existing composite insulators ages under high temperature and harsh weather conditions, resulting in a decrease in water-blocking sealing performance, affecting its service life and the stability of the transmission line.

Method used

Modified alumina microspheres prepared from glucose solution and aluminum nitrate and other raw materials are formed to form a porous hollow structure and nano cerium oxide film layer, combined with vinyl trimethoxysilane and azodiisobutyronitrile to prepare excellent high temperature resistance and hydrophobic insulator adhesives used to inject into the gap between the metal and mandrel of composite insulators.

Benefits of technology

It significantly improves the high temperature resistance and insulation performance of composite insulators, improves the water-resistance sealing performance, and provides excellent bonding performance for a long time, extends the service life and improves the stability of the transmission line.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a composite insulator and a preparation method thereof. The composite insulator comprises an upper gold piece, a lower gold piece, an insulator main body and an umbrella skirt, and an insulator adhesive is arranged between the upper gold piece and the end of the insulator main body and between the lower gold piece and the end of the insulator main body. The insulator adhesive is prepared from the following raw materials in parts by weight: 60 to 90 parts of E51 type bisphenol A epoxy resin, 20 to 30 parts of tetraglycidylxylenediamine, 20 to 40 parts of allyl glycidyl ether, 15 to 20 parts of dicyandiamide, 4 to 6 parts of graphite-like carbon nitride, 5 to 8 parts of functional additive, 2 to 5 parts of 3-glycidylpropyltrimethoxysilane, 15 to 25 parts of elastic reinforcement, 30 to 100 parts of curing agent, 1.5 to 2.5 parts of curing accelerator and 10 parts of curing accelerator. 20 parts of carboxyl-terminated liquid nitrile rubber and 150-300 parts of an organic solvent. The composite insulator has the advantages that the high-temperature resistance and the insulation performance of the composite insulator can be improved, and the water-blocking sealing performance of the composite insulator can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of insulators, in particular to a composite insulator and a preparation method thereof. Background Art

[0002] Insulators (also known as insulators) are a special type of insulating control that plays an important role in overhead transmission lines. Insulators can be divided into suspension insulators and post insulators according to different installation methods; they can be divided into porcelain insulators, glass insulators and composite insulators according to different insulating materials used.

[0003] The composite insulator is mainly composed of a silicone rubber shed, an epoxy resin fiberglass core rod and hardware at both ends. For the composite insulator with flange connection at the end, the installation process is as follows: after the hardware flange and the core rod are assembled, it is necessary to inject potting glue into the flange to fill the gap between the hardware flange and the core rod, prevent water vapor from entering the interface between the hardware and the core rod, thereby reducing the aging rate of the hardware and the core rod. In the prior art, the potting glue filled between the core rod and the flange is mostly potted with epoxy resin glue, and the epoxy resin glue in the prior art has relatively poor water-blocking sealing performance and high temperature resistance. It is under high electric field strength for a long time, and it ages after being heated, which significantly reduces its bonding performance, which affects its water-blocking sealing performance and service life to a certain extent. In addition, when the composite insulator is in operation for a long time, the surface will inevitably be severely eroded by severe weather or natural phenomena such as haze, acid rain, rain, ice, snow melting agent, etc., so that moisture or water enters the crimping interface between the hardware and the core rod, accelerating the wet heat aging of the epoxy resin to reduce its insulation performance, and also increasing the risk of power transmission failure, affecting the stable operation of the power transmission line. Based on this, the present invention provides a composite insulator and a preparation method thereof to solve the above-mentioned technical problems. Summary of the invention

[0004] The purpose of the present invention is to provide a composite insulator and a preparation method thereof, which can not only effectively improve its high temperature resistance and insulation performance, but also significantly improve its water-blocking and sealing performance, so that it has excellent bonding performance for a long time, and effectively ensures its quality.

[0005] To achieve the above object, the present invention provides the following technical solutions: A composite insulator comprises an upper metal piece, a lower metal piece, an insulator body and an umbrella skirt, wherein the upper metal piece is arranged at the upper end of the insulator body, the lower metal piece is arranged at the lower end of the insulator body, and the umbrella skirt is arranged on the outside of the insulator body; an insulator adhesive is poured between the upper metal piece and the upper end of the insulator body, and between the lower metal piece and the lower end of the insulator body, and the insulator adhesive is composed of the following raw materials in parts by weight: 60 to 90 parts of E51 type Bisphenol A epoxy resin, 20-30 parts of tetraglycidyl xylene diamine, 20-40 parts of allyl glycidyl ether, 15-20 parts of melamine, 4-6 parts of graphite-like carbon nitride, 5-8 parts of functional additives, 2-5 parts of 3-glycidylpropyltrimethoxysilane, 15-25 parts of elastic reinforcement, 30-100 parts of curing agent, 1.5-2.5 parts of curing accelerator, 10-20 parts of carboxyl-terminated liquid nitrile rubber and 150-300 parts of organic solvent.

[0006] Furthermore, the preparation method of the functional additive comprises the following steps: adding modified alumina microspheres into tetrahydrofuran at a dosage ratio of 30 to 80 g / L, adding vinyltrimethoxysilane in an amount of 0.8 to 1.2 times the mass of the modified alumina microspheres after uniform dispersion, and stirring the reaction at a temperature of 30 to 40° C. for 3 to 5 hours; after the reaction is completed, adding methyl methacrylate in an amount of 0.3 to 0.5 times the mass of the modified alumina microspheres and styrene in an amount of 0.2 to 0.3 times, respectively, after stirring, adding azobisisobutyronitrile in an amount of 0.1 to 0.2 times the mass of methyl methacrylate after uniform dispersion, and keeping the reaction at a temperature of 65 to 85° C. for 5 to 8 hours; after the reaction is completed, filtering, washing and drying the resulting components in turn to obtain the functional additive.

[0007] Furthermore, the preparation method of the modified alumina microspheres includes the following steps: adding 2-3% of polyvinyl pyrrolidone to a 10-30wt% aqueous dispersion of alumina microspheres, heating to 50-60°C after uniform dispersion, and continuing stirring for 40-60 minutes; then adding a cerium nitrate aqueous solution with a volume of 0.2-0.4 times that of the aqueous dispersion of alumina microspheres and a concentration of 1-1.5 mol / L, mixing evenly and slowly adding 1-1.5 mol / L of sodium hydroxide aqueous solution until the pH of the obtained mixed component is 8.0-8.5; then standing at room temperature for 20-30 hours, filtering it after standing, washing the obtained filter cake and then calcining it at a temperature of 130-150°C for 3-5 hours to obtain modified alumina microspheres.

[0008] Furthermore, the preparation method of the alumina microspheres includes the following steps: heat treating a 1-1.5 mol / L glucose solution in an oven at 170-200°C for 6-10 hours, centrifuging the solution after the heat treatment is completed, washing the filter cake with deionized water and anhydrous ethanol 2-3 times each, and then drying the solution at 70-80°C; putting the solid powder obtained after drying into a 0.2-0.5 mol / L aluminum nitrate aqueous solution, ultrasonically mixing the solution for 20-30 minutes, and standing the solution at 30-50°C for 15-25 hours; filtering the solution after standing, and drying and high-temperature sintering the filter cake to obtain alumina microspheres; wherein the amount of the solid powder is 8-12% of the mass of the aluminum nitrate.

[0009] Furthermore, the specific steps of high-temperature sintering are: transferring the dried filter cake into a high-temperature sintering device, heating it to 300-350°C at a rate of 2-5°C / min under nitrogen protection, and keeping it warm for 3-4 hours; then heating it to 400-450°C at a rate of 2-5°C / min, and keeping it warm for 3-4 hours; finally, heating it to 500-550°C at a rate of 2-5 / min, switching to oxygen, and keeping it warm at this temperature for 3-5 hours.

[0010] Furthermore, the elastic reinforcement is selected from any one of polybutadiene rubber / polymethyl methacrylate core-shell rubber and styrene-butadiene rubber / polymethyl methacrylate core-shell rubber; and its average particle size is 10-20 μm.

[0011] Furthermore, the curing agent is selected from any one of methylhexahydrophthalic anhydride and methyltetrahydrophthalic anhydride.

[0012] Furthermore, the curing accelerator is selected from any one of 2-ethyl-4-methylimidazole, dimethylbenzylamine, 2-methylimidazole, and tris(dimethylaminomethyl)phenol.

[0013] Furthermore, the organic solvent is selected from any one of toluene, dimethyl carbonate and xylene.

[0014] A preparation method of a composite insulator comprises the following steps: crimping an upper metal piece with an upper end of an insulator body, crimping a lower metal piece with a lower end of the insulator body, injecting an insulator adhesive into a gap between an inner wall of the upper metal piece and an outer wall of an upper end of the insulator body; injecting an insulator adhesive into a gap between an inner wall of the lower metal piece and an outer wall of a lower end of the insulator body to form a composite insulator blank; storing the composite insulator blank for more than 48 hours at a temperature of 20 to 30 degrees Celsius, placing the composite insulator blank into a mold, thermoforming an shed, and obtaining a composite insulator after cooling.

[0015] Compared with the prior art, the present invention has the following beneficial effects: The insulator adhesive of the present invention uses glucose solution and aluminum nitrate as raw materials to prepare alumina microspheres with a porous hollow structure. Then the prepared alumina microspheres are put into water and polyvinyl pyrrolidone is added. After uniform dispersion, cerium nitrate aqueous solution and sodium hydroxide aqueous solution are added in sequence, and finally a dense nano-cerium oxide film layer is deposited on the surface and inner cavity wall of the alumina microspheres to prepare modified alumina microspheres. Alumina nano-microspheres themselves have excellent high temperature resistance, and the mutual synergy and cooperation between their hollow porous structure and the nano-cerium oxide film layer further improve their high temperature resistance, so that the prepared modified alumina microspheres have better high temperature resistance and electrical insulation performance.

[0016] Then the modified alumina microspheres are put into tetrahydrofuran and vinyl trimethoxysilane is added, so that the vinyl trimethoxysilane reacts chemically with the nano cerium oxide film layer on the surface of the modified alumina microspheres and bonds, and finally the vinyl trimethoxysilane successfully bonds to the surface of the nano cerium oxide. After the reaction is completed, methyl methacrylate and styrene are added thereto in sequence, and after stirring evenly, methyl methacrylate and styrene react chemically with the vinyl trimethoxysilane on the modified alumina microspheres under the action of azobisisobutyronitrile, and finally methyl methacrylate and styrene are successfully grafted on the surface of the modified alumina microspheres under the "bridge" action of vinyl trimethoxysilane, so that the hydrophobic properties of the prepared functional additives are significantly improved. The composite insulator prepared with the above-mentioned insulator adhesive can not only effectively improve the high temperature resistance and insulation properties of the composite insulator, but also significantly improve the water-blocking and sealing properties of the composite insulator, so that the composite insulator has excellent bonding properties for a long time, and effectively guarantees its quality. DETAILED DESCRIPTION

[0017] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0018] Embodiment 1: A composite insulator, comprising an upper metal piece, a lower metal piece, an insulator body and an umbrella skirt, wherein the upper metal piece is arranged at the upper end of the insulator body, the lower metal piece is arranged at the lower end of the insulator body, and the umbrella skirt is arranged on the outside of the insulator body; an insulator adhesive is poured between the inner wall of the upper metal piece and the upper outer wall of the insulator body, and between the inner wall of the lower metal piece and the lower outer wall of the insulator body, wherein the insulator adhesive is composed of the following raw materials in parts by weight: 60 parts of E51 bisphenol A epoxy resin; Resin, 20 parts of tetraglycidyl xylene diamine, 20 parts of allyl glycidyl ether, 15 parts of melamine, 4 parts of graphite-like carbon nitride, 5 parts of functional additives, 2 parts of 3-glycidylpropyltrimethoxysilane, 15 parts of elastic reinforcement, 30 parts of methylhexahydrophthalic anhydride, 1.5 parts of 2-ethyl-4-methylimidazole, 10 parts of terminal carboxyl liquid nitrile rubber and 150 parts of toluene; wherein the elastic reinforcement is selected from polybutadiene rubber / polymethyl methacrylate core-shell rubber; and its average particle size is 10μm.

[0019] The preparation method of the functional additive comprises the following steps: adding modified alumina microspheres into tetrahydrofuran at a dosage ratio of 30 g / L, adding vinyltrimethoxysilane with a mass of 0.8 times that of the modified alumina microspheres after uniform dispersion, and stirring for reaction at a temperature of 30°C for 3 hours; after the reaction is completed, adding methyl methacrylate with a mass of 0.3 times that of the modified alumina microspheres and styrene with a mass of 0.2 times that of the modified alumina microspheres respectively, stirring evenly, and then adding azobisisobutyronitrile with a mass of 0.1 times that of methyl methacrylate, and after uniform dispersion, heat-insulating for reaction at a temperature of 65°C for 5 hours; after the reaction is completed, filtering, washing and drying the obtained product components in turn to obtain the functional additive.

[0020] The preparation method of modified alumina microspheres comprises the following steps: adding 2% polyvinyl pyrrolidone by weight to a 10wt% aqueous phase dispersion of alumina microspheres, heating to 50°C after uniform dispersion, and continuing stirring for 40 minutes; then adding a 1mol / L cerium nitrate aqueous solution with a volume 0.2 times that of the aqueous phase dispersion of alumina microspheres, mixing evenly and slowly adding a 1mol / L sodium hydroxide aqueous solution until the pH of the obtained mixed component is 8.0; then standing at room temperature for 20 hours, filtering after standing, washing the obtained filter cake and then calcining at 130°C for 5 hours to obtain modified alumina microspheres.

[0021] The preparation method of alumina microspheres comprises the following steps: heat treating a 1 mol / L glucose solution in an oven at 170°C for 6 hours, centrifugally separating the solution after the heat treatment, washing the obtained filter cake with deionized water and anhydrous ethanol twice respectively, and then drying the solution at 70°C; putting the obtained solid powder into a 0.2 mol / L aluminum nitrate aqueous solution, ultrasonically mixing the solution for 20 minutes, and standing the solution at 30°C for 15 hours; filtering the solution after the standing is completed, and obtaining the filter cake through drying and high-temperature sintering to obtain alumina microspheres; wherein the amount of the solid powder is 8% of the mass of the aluminum nitrate.

[0022] The specific steps of high-temperature sintering are as follows: the dried filter cake is transferred into a high-temperature sintering device, and under nitrogen protection, the temperature is raised to 300°C at a rate of 2°C / min, and the temperature is kept for 3 hours; then the temperature is raised to 400°C at a rate of 2°C / min, and the temperature is kept for 3 hours; finally, the temperature is raised to 500°C at a rate of 2 / min, oxygen is passed, and the temperature is kept for 3 hours at this temperature.

[0023] A preparation method of a composite insulator comprises the following steps: crimping an upper metal piece with an upper end crimped on an insulator body, crimping a lower metal piece with a lower end crimped on an insulator body, injecting an insulator adhesive into a gap between an inner wall of the upper metal piece and an outer wall of an upper end of the insulator body, including but not limited to a reserved hole on the upper metal piece, and then injecting the insulator adhesive from the reserved hole; injecting the insulator adhesive into a gap between an inner wall of the lower metal piece and an outer wall of a lower end of the insulator body, including but not limited to a reserved hole on the lower metal piece, and then injecting the insulator adhesive from the reserved hole; making a composite insulator blank; storing the composite insulator blank for more than 48 hours under an environmental condition of 20 degrees Celsius to 30 degrees Celsius, and then putting the composite insulator blank into a mold, thermoforming an shed, and obtaining a composite insulator after cooling.

[0024] The preparation method of the insulator adhesive of the present invention comprises the following steps: weighing various raw materials according to the formula amount, then adding epoxy resin into an organic solvent, adding the remaining raw materials after the epoxy resin is dissolved, and mixing and stirring to obtain a mixed adhesive material which is a composite insulator.

[0025] Embodiment 2: The preparation method of a composite insulator provided in this embodiment is basically the same as that in Embodiment 1, except that the specific composition of the insulator adhesive and the preparation method of the functional additive are not exactly the same. The specific composition of the composite insulator raw material and the preparation method of the functional additive in this embodiment are as follows: A composite insulator comprises an upper metal piece, a lower metal piece, an insulator body and an umbrella skirt, wherein the upper metal piece is arranged at the upper end of the insulator body, the lower metal piece is arranged at the lower end of the insulator body, and the umbrella skirt is arranged on the outer side of the insulator body; an insulator adhesive is poured between the inner wall of the upper metal piece and the upper outer wall of the insulator body, and between the inner wall of the lower metal piece and the lower outer wall of the insulator body, wherein the insulator adhesive is composed of the following raw materials in parts by weight: 80 parts of E51 bisphenol A epoxy resin; Resin, 25 parts of tetraglycidyl xylene diamine, 30 parts of allyl glycidyl ether, 15 parts of melamine, 5 parts of graphite-like carbon nitride, 6 parts of functional additives, 3 parts of 3-glycidylpropyltrimethoxysilane, 20 parts of elastic reinforcement, 60 parts of methyltetrahydrophthalic anhydride, 2.0 parts of dimethylbenzylamine, 15 parts of carboxyl-terminated liquid nitrile rubber and 250 parts of dimethyl carbonate; wherein the elastic reinforcement is selected from styrene-butadiene rubber / polymethyl methacrylate core-shell rubber; and its average particle size is 15μm.

[0026] The preparation method of the functional additive comprises the following steps: adding modified alumina microspheres into tetrahydrofuran at a dosage ratio of 50 g / L, adding vinyltrimethoxysilane in an amount equal to that of the modified alumina microspheres after uniform dispersion, and stirring for reaction at a temperature of 35°C for 4 hours; after the reaction is completed, adding methyl methacrylate and styrene in an amount of 0.4 times the mass of the modified alumina microspheres respectively, stirring evenly, and then adding azobisisobutyronitrile in an amount of 0.15 times the mass of methyl methacrylate, and after uniform dispersion, heat-insulating for reaction at a temperature of 75°C for 6 hours; after the reaction is completed, filtering, washing and drying the obtained product components in turn to obtain the functional additive.

[0027] The preparation method of modified alumina microspheres comprises the following steps: adding 3% polyvinyl pyrrolidone by weight to a 20wt% aqueous phase dispersion of alumina microspheres, heating to 55°C after uniform dispersion, and continuing stirring for 50 minutes; then adding a 1.5mol / L cerium nitrate aqueous solution with a volume 0.3 times that of the aqueous phase dispersion of alumina microspheres, mixing evenly and slowly adding a 1.5mol / L sodium hydroxide aqueous solution until the pH of the obtained mixed component is 8.3; then standing at room temperature for 25 hours, filtering after standing, washing the obtained filter cake and then calcining at 140°C for 45 hours to obtain modified alumina microspheres.

[0028] The preparation method of alumina microspheres comprises the following steps: heat treating a 1.5 mol / L glucose solution in an oven at 180°C for 8 hours, centrifuging the solution after the heat treatment is completed, washing the obtained filter cake with deionized water and anhydrous ethanol for 3 times respectively, and then drying the solution at 75°C; putting the obtained solid powder into a 0.3 mol / L aluminum nitrate aqueous solution, ultrasonically mixing the solution for 25 minutes, and standing the solution at 40°C for 20 hours; filtering the solution after the standing is completed, and obtaining the filter cake through drying and high-temperature sintering to obtain alumina microspheres; wherein the amount of the solid powder is 10% of the mass of the aluminum nitrate.

[0029] The specific steps of high-temperature sintering are as follows: the dried filter cake is transferred into a high-temperature sintering device, and under nitrogen protection, the temperature is raised to 350°C at a rate of 5°C / min, and the temperature is kept for 4 hours; then the temperature is raised to 450°C at a rate of 5°C / min, and the temperature is kept for 4 hours; finally, when the temperature is raised to 550°C at a rate of 5 / min, oxygen is passed, and the temperature is kept at this temperature for 5 hours.

[0030] Embodiment 3: The preparation method of a composite insulator provided in this embodiment is basically the same as that in Embodiment 1, except that the specific composition of the insulator adhesive and the preparation method of the functional additive are not exactly the same. The specific composition of the composite insulator raw material and the preparation method of the functional additive in this embodiment are as follows: A composite insulator comprises an upper metal piece, a lower metal piece, an insulator body and an umbrella skirt, wherein the upper metal piece is arranged at the upper end of the insulator body, the lower metal piece is arranged at the lower end of the insulator body, and the umbrella skirt is arranged at the outer side of the insulator body; an insulator adhesive is poured between the inner wall of the upper metal piece and the upper outer wall of the insulator body, and between the inner wall of the lower metal piece and the lower outer wall of the insulator body, wherein the insulator adhesive is composed of the following raw materials in parts by weight: 90 parts of E51 bisphenol A epoxy resin; The invention discloses a novel nanostructured carbon foam comprising the following components: a nanostructured carbon foam, ...

[0031] The preparation method of the functional additive comprises the following steps: adding modified alumina microspheres into tetrahydrofuran at a dosage ratio of 80 g / L, adding vinyltrimethoxysilane with a mass of 1.2 times that of the modified alumina microspheres after uniform dispersion, and stirring and reacting at a temperature of 40°C for 5 hours; after the reaction is completed, adding methyl methacrylate with a mass of 0.5 times that of the modified alumina microspheres and styrene with a mass of 0.3 times that of the modified alumina microspheres respectively, stirring evenly, and then adding azobisisobutyronitrile with a mass of 0.2 times that of methyl methacrylate, and after uniform dispersion, heat-insulating and reacting at a temperature of 85°C for 8 hours; after the reaction is completed, filtering, washing and drying the obtained product components in turn to obtain the functional additive.

[0032] The preparation method of modified alumina microspheres comprises the following steps: adding 3% polyvinyl pyrrolidone by weight to a 30wt% aqueous phase dispersion of alumina microspheres, heating to 60°C after uniform dispersion, and continuing stirring for 60 minutes; then adding a 1.5mol / L cerium nitrate aqueous solution with a volume 0.4 times that of the aqueous phase dispersion of alumina microspheres, mixing evenly and slowly adding a 1.5mol / L sodium hydroxide aqueous solution until the pH of the obtained mixed component is 8.5; then standing at room temperature for 30 hours, filtering after standing, washing the obtained filter cake and then calcining at 150°C for 5 hours to obtain modified alumina microspheres.

[0033] The preparation method of alumina microspheres comprises the following steps: heat treating a 1.5 mol / L glucose solution in an oven at 200°C for 10 hours, centrifugally separating the solution after the heat treatment, washing the obtained filter cake with deionized water and anhydrous ethanol for 3 times respectively, and then drying the solution at 80°C; putting the obtained solid powder into a 0.5 mol / L aluminum nitrate aqueous solution, ultrasonically mixing the solution for 30 minutes, and standing the solution at 50°C for 25 hours; filtering the solution after the standing is completed, and obtaining the filter cake through drying and high-temperature sintering to obtain alumina microspheres; wherein the amount of the solid powder used is 12% of the mass of the aluminum nitrate.

[0034] The specific steps of high-temperature sintering are as follows: the dried filter cake is transferred into a high-temperature sintering device, and under nitrogen protection, the temperature is raised to 350°C at a rate of 5°C / min, and the temperature is kept for 4 hours; then the temperature is raised to 450°C at a rate of 5°C / min, and the temperature is kept for 4 hours; finally, when the temperature is raised to 550°C at a rate of 5 / min, oxygen is passed, and the temperature is kept at this temperature for 5 hours.

[0035] Comparative Example 1 is different from Example 1 in that an equal amount of modified alumina microspheres is used in the insulator adhesive in the composite insulator to replace the functional additive.

[0036] Comparative Example 2 is different from Example 1 in that an equal amount of alumina microspheres are used in the insulator adhesive in the composite insulator to replace the functional additive.

[0037] Performance test: The following tests were performed on the relevant performances of the composite insulator samples provided in Examples 1 to 3 and Comparative Examples 1 to 2: 1. Tensile strength test: refer to GB / T 2567-2008 resin casting performance test method.

[0038] 2. Glass transition temperature test: refer to GB / T 19466.2 Plastics Differential Scanning Calorimetry (DSC) Part 2: Determination of glass transition temperature, the heating rate is 20℃ / min.

[0039] 3. Water absorption test: Store each group of composite insulator samples at a humidity of 90% and a temperature of 60°C for 180 days, and then test the water absorption of each group of composite insulator samples.

[0040] 4. Gas sealing test: Install the insulating part with the double-layer sealing ring at the end of the metal gas chamber tooling. The gas chamber is equipped with a precision pressure detection gauge. Fill the gas chamber with 0.8MPa SF6 gas in a constant temperature room until it reaches a stable state. After 8 hours, observe whether the gas pressure changes. If there is no change in gas pressure, it is stable, and if there is a change in gas pressure, it is unstable.

[0041] 5. Mixture viscosity test at 25°C: refer to GB / T 22314-2008 Plastic epoxy resin viscosity determination method.

[0042] The test data obtained above are recorded in the following Table 1: Table 1

[0043] By comparing and analyzing the relevant data in Table 1, it can be seen that the functional additive prepared by the present invention not only has excellent high temperature resistance, but also has good hydrophobicity. When used as a potting material for composite insulators, it can not only effectively improve its high temperature resistance and insulation performance, but also significantly improve its water blocking and sealing performance, so that it has excellent bonding performance for a long time, and effectively guarantees its quality. This shows that the composite insulator and the preparation method thereof provided by the present invention have a broader market prospect and are more suitable for promotion.

[0044] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0045] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. A composite insulator, comprising an upper metal part, a lower metal part, an insulator body and an shed, wherein the upper metal part is arranged at the upper end of the insulator body, the lower metal part is arranged at the lower end of the insulator body, and the shed is arranged on the outer side of the insulator body; characterized in that: An insulator adhesive is poured between the upper metal piece and the upper end of the insulator body, and between the lower metal piece and the lower end of the insulator body. The insulator adhesive is composed of the following raw materials in parts by weight: 60 to 90 parts of E51 bisphenol A epoxy resin, 20 to 30 parts of tetraglycidyl xylene diamine, 20 to 40 parts of allyl glycidyl ether, 15 to 20 parts of melamine, 4 to 6 parts of graphite-like carbon nitride, 5 to 8 parts of functional additives, 2 to 5 parts of 3-glycidylpropyltrimethoxysilane, 15 to 25 parts of elastic reinforcement, 30 to 100 parts of curing agent, 1.5 to 2.5 parts of curing accelerator, 10 to 20 parts of carboxyl-terminated liquid nitrile rubber and 150 to 300 parts of organic solvent.

2. A composite insulator according to claim 1, characterized in that: The preparation method of the functional additive comprises the following steps: adding modified alumina microspheres into tetrahydrofuran at a dosage ratio of 30 to 80 g / L, adding vinyl trimethoxysilane in an amount of 0.8 to 1.2 times the mass of the modified alumina microspheres after uniform dispersion, and stirring for reaction at a temperature of 30 to 40° C. for 3 to 5 hours; after the reaction is completed, adding methyl methacrylate in an amount of 0.3 to 0.5 times the mass of the modified alumina microspheres and styrene in an amount of 0.2 to 0.3 times the mass of the modified alumina microspheres respectively, stirring evenly, and then adding azobisisobutyronitrile in an amount of 0.1 to 0.2 times the mass of methyl methacrylate, uniformly dispersing, and heat-insulating for reaction at a temperature of 65 to 85° C. for 5 to 8 hours; after the reaction is completed, filtering, washing and drying the obtained product components in sequence to obtain the functional additive.

3. A composite insulator according to claim 2, characterized in that: The preparation method of the modified alumina microspheres comprises the following steps: adding 2-3% polyvinyl pyrrolidone by weight to a 10-30wt% aqueous phase dispersion of alumina microspheres, heating to 50-60°C after uniform dispersion, and continuing stirring for 40-60min; then adding a cerium nitrate aqueous solution with a volume of 0.2-0.4 times that of the aqueous phase dispersion of the alumina microspheres and a concentration of 1-1.5mol / L, mixing evenly and slowly adding a 1-1.5mol / L sodium hydroxide aqueous solution until the pH of the obtained mixed component is 8.0-8.5; then standing at room temperature for 20-30h, filtering after standing, washing the obtained filter cake and then calcining at a temperature of 130-150°C for 3-5h to obtain the modified alumina microspheres.

4. A composite insulator according to claim 3, characterized in that: The preparation method of the alumina microspheres comprises the following steps: heat treating a 1-1.5 mol / L glucose solution in an oven at 170-200°C for 6-10 hours, centrifugally separating the solution after the heat treatment, washing the obtained filter cake with deionized water and anhydrous ethanol for 2-3 times respectively, and then drying the solution at 70-80°C; putting the obtained solid powder into a 0.2-0.5 mol / L aluminum nitrate aqueous solution, ultrasonically mixing the solution for 20-30 minutes, and standing the solution at 30-50°C for 15-25 hours; filtering the solution after the standing is completed, and drying and high-temperature sintering the obtained filter cake to obtain the alumina microspheres; wherein the amount of the solid powder is 8-12% of the mass of the aluminum nitrate.

5. A composite insulator according to claim 4, characterized in that: The specific steps of high-temperature sintering are: transferring the dried filter cake into a high-temperature sintering device, heating it to 300-350°C at a rate of 2-5°C / min under nitrogen protection, and keeping it warm for 3-4 hours; then heating it to 400-450°C at a rate of 2-5°C / min, and keeping it warm for 3-4 hours; finally heating it to 500-550°C at a rate of 2-5 / min, switching to oxygen, and keeping it warm at this temperature for 3-5 hours.

6. A composite insulator according to claim 1, characterized in that: The elastic reinforcement is selected from any one of polybutadiene rubber / polymethyl methacrylate core-shell rubber and styrene-butadiene rubber / polymethyl methacrylate core-shell rubber, and its average particle size is 10-20 μm.

7. A composite insulator according to claim 1, characterized in that: The curing agent is selected from any one of methylhexahydrophthalic anhydride and methyltetrahydrophthalic anhydride.

8. A composite insulator according to claim 1, characterized in that: The curing accelerator is selected from any one of 2-ethyl-4-methylimidazole, dimethylbenzylamine, 2-methylimidazole, and tris(dimethylaminomethyl)phenol.

9. A composite insulator according to claim 1, characterized in that: The organic solvent is selected from any one of toluene, dimethyl carbonate and xylene.

10. The method for preparing a composite insulator according to any one of claims 1 to 9, characterized in that: The method comprises the following steps: crimping an upper metal piece with an upper end of an insulator body, crimping a lower metal piece with a lower end of an insulator body, injecting an insulator adhesive into a gap between an inner wall of the upper metal piece and an outer wall of an upper end of the insulator body; injecting an insulator adhesive into a gap between an inner wall of the lower metal piece and an outer wall of a lower end of the insulator body to form a composite insulator blank; storing the composite insulator blank for more than 48 hours at a temperature of 20 to 30 degrees Celsius, placing the composite insulator blank into a mold, thermoforming an shed, and obtaining a composite insulator after cooling.

Citation Information

Patent Citations

  • Epoxy resin pouring sealant for composite insulator and preparation method of epoxy resin pouring sealant

    CN103289626A

  • Fast curing epoxy resin composition and preparation method thereof

    CN108794983A

  • Rod-type porcelain composite insulator for subway tunnel

    CN110428942A

  • Adhesive with efficient barrier property, preparation method and application of adhesive in composite insulator

    CN113930203A

  • Epoxy insulator and manufacturing method thereof

    KR101797439B1

Cited By

  • Far-stable near-solid type nano sand consolidation agent and preparation method thereof

    CN120888290A